Hubungan Pengetahuan dan Peran Keluarga dengan Kepatuhan Melakukan Pemeriksaan IVA pada Ibu PUS Prakonsepsi di UPT Puskesmas Ajangale - Fatimah Jamir; Andi Tenri Angka; Ummu Kalsum; Syarifah sahirah (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
VIA is a simple test. The VIA test is a method for early detection of cervical cancer by applying 3-5% acetic acid or vinegar. It has a 96% accuracy rate; abnormal areas will turn white. If there is no color change, it can be assumed that there is no cervical infection. This VIA test is important for fertile couples, including preconception women with PUS. To determine the relationship between knowledge and family role with compliance with VIA testing in preconception women with PUS at the Ajangale Community Health Center (UPT). This study used an observational research method with a cross-sectional approach. The population in this study were all PUS women aged 20-35 years at the UPT Ajangale Community Health Center. Sampling was carried out using a total sampling technique, obtaining 30 respondents. Data collection was carried out using a questionnaire. The collected data were then processed and analyzed using the SPSS statistical program and analyzed using the chi-square test. The study showed a relationship between compliance with VIA testing and two variables studied: knowledge (p=0.000) and family role (0.000). Compliance with VIA testing in preconceptional women with PUS is influenced by both knowledge and family role. This study focused on preconception women with PUS at the Ajangale Community Health Center, aiming to understand the factors that influence their compliance with VIA testing. By analyzing the relationship between knowledge and family role with VIA compliance, the study highlights the importance of educating women about the benefits of early cervical cancer detection and the pivotal role families play in supporting health-seeking behaviors.